Fungsi Orang Tua dalam Mendampingi Pembelajaran Anak Usia Belajar Selama Pandemi Covid-19 - Kamelia, Kamelia; Lindawati, Yustika Irfani (Lembaga Yasin AlSys, 2022)
This study aims to discuss how parents respond to accompanying children in participating in distance learning in the era of the Covid-19 pandemic which is carried out virtually, this aims so that every parent can observe every development in their children and also help monitor the development of achievements owned by children which in the current era of the Covid-19 pandemic can only follow and do learning virtually. In addition, this study also aims to describe how parents respond or views to educational status are carried out virtually. The method used in this study is a qualitative method with the data obtained is descriptive of this type of research to provide a good study Comprehensive and specific related to events or phenomena that occur from everyday life. Parents are one of the subjects that play an important role in supporting children's learning during the Covid-19 pandemic, but the many jobs that require parents to keep working become a deepening in terms of accompanying children when participating in learning, accompanying a child in every day is an obligation for every parent in carrying out his role, at this time the role of parents is very much needed this because parents are the closest members who can exert a very big influence for their children.